Implementasi Program Pendampingan Desa Dalam Meningkatkan Ketahanan Pangan - Riyan Saputra (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Implementation of the Village Assistance Program is a very important process when talking about Program Implementation, the steps for implementing activities in an effort to achieve the goals of the program itself, one of the important components in an implementation is the efforts made by the authorities to achieve the desired goals. . This research uses descriptive qualitative method. namely research conducted by describing a situation or event that occurs in the field based on the facts that occurred as it should. Then put it in writing with an attempt to draw conclusions. The purpose of this study was to find out how the Implementation of the Village Assistance Program in Improving Food Security in Bukit Village, Pelawan District, Sarolangun Regency. This study uses Village Law Regulation No. 06 of 2014 and is strengthened by PermenDes No. 03 of 2015 concerning Disadvantaged Village Builders and Transmigration. By using the theory of Siagian. To obtain data from this research by using interviews, observation, and documentation. The obstacles in implementing the Village Assistance Program are the lack of socialization, communication, and inadequate resources. This research is a form of evaluation material for the Village Assistance Program. And as input for the Village Government in Implementing the Village Assistance Program in Improving Food Security.